PERAN MASJID AL FURQAN DALAM PENGUATAN PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS PENDIDIKAN INDONESIA - Alden Aditia Maulana; Edi Suresman; Agus Fakhruddin (Universitas Pendidikan Indonesia, 2021)
AbstractThis research is motivated by the importance of personal coaching which is followed up with the development of Muslims. Mosques can be used as a means of fostering Islamic community education by strengthening Islamic Religious Education. Because the mosque in addition to functioning as a place of worship, but also acts as a center of Islamic education. The history of the mosque has long been used as a place of education since the early centuries of the development of Islamic da'wah. Al-Furqan Mosque, UPI is one of the religious campus mosques. In general, this study aims to describe the role of the Al-Furqan Mosque in strengthening Islamic education at the upi Specifically, the purpose of this study is to describe: (1) the profile of the Al-Furqan Mosque; (2) goals; (3) subject matter; (4) process; (5) constraints and support; (6) Results of Strengthening Islamic Religious Education at the Al-Furqan Mosque, UPI. This study uses a qualitative approach with descriptive research methods. The participants in this study were Takmir Al-Furqan, study presenter, students/congregations and on-campus organizations. Data collection techniques using interview studies, observation, questionnaires and documentation. Data analysis is in the form of data reduction, data display, and data verification. The results of the research that have been achieved are in the form of an overview of the role of the Al-Furqan Mosque in strengthening Islamic education at the Indonesian Education University. The results of the study indicate that the Takmir Al-Furqan has a very important role in it, which is realized through scheduled and incidental assessment programs. The purpose of this program is to create a religious atmosphere for religious people on campus in accordance Indonesia University Of Education's motto, namely Education, Scientific and Religious. In this activity there are 3 inhibiting factors and 6 supporting factors. There are subject matter on Aqidah, Morals, Shari'a, Islamic Shari'a and History and using relevant sources (references) produce 3 pillars of normative values for the campus community, namely I'tiqadiyah, Khuluqiyah, and Amaliyah.Keywords: Coaching, Religion, Campus.AbstrakPenelitian ini dilatar belakangi oleh pentingnya pembinaaan pribadi yang ditindaklanjuti kearah pembinaan suatu masyarakat Islam. Masjid dapat digunakan sebagai sarana pembinaan pendidikan masyarakat Islam dengan cara penguatan Pendidikan Agama Islam. Karena Masjid selain berfungsi sebagai tempat ibadah, tetapi berperan sebagai pusat pendidikan Agama Islam. Secara umum penelitian ini bertujuan untuk mendeskripsikan peran Masjid Al-Furqan dalam penguatan PAI di UPI. Secara khusus tujuan penelitian ini adalah untuk mendeskripsikan: (1) profil Masjid Al-Furqan; (2) tujuan; (3) materi; (4) proses; (5) Kendala dan pendukung ; (6) hasil dari penguatan PAI di Masjid Al-Furqan UPI. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi deskriptif. Partisipan dalam penelitian ini adalah Takmir Al-Furqan, pemateri kajian, mahasiswa/jemaah dan Organisasi Intra universeter. Teknik pengumpulan data menggunakan studi wawancara, observasi, kuisioner dan dokumentasi. Analisis data dalam bentuk reduksi data, display data, dan verifikasi data. Hasil Penelitian menunjukan bahwa Takmir Masjid Al-Furqan sangat berperan didalamnya dengan membuat program kajian rutinan dan insidental. Tujuannya yaitu untuk terciptanya suasana keagamaan masyarakat kampus yang religius agar sesuai dengan motto UPI. Terdapat 3 faktor kendala dan 6 faktor pendukung. Pemberian materi Aqidah, akhlak, syariat, hukum Islam, Tarikh serta menggunakan sumber(referensi) yang relevan menghasilkan 3 pilar nilai normatif terhadap Masyarakat kampus yaitu I'tiqadiyah, Khuluqiyah, dan Amaliyah.Kata kunci : Pembinaan, Religius , Kampus.